Evaluation of Mental Health in the Paraplegic Veterans and Disables; A Case Study of Mazandaran Province - H. Tahmasebi; S. Pourhosein; S. Talebi; A. Poorkhiz (Afarand Scholarly Publishing Institute, 2019)
Aims: The mental health of any person is affected by disabilities. These effects are not the same in persons with disabilities due to the accidence and in the veterans. The aim of this study was to investigate the mental health in the paraplegic veterans and disables. Instruments & Methods: This descriptive cross-sectional study was conducted in 2016 amoung 29 paraplegic veterans and 106 paraplegic disables having been supported by the Martyrs and Veterans Foundation of Mazandaran Province. The samples were selected by stratified random sampling method. Data was collected by a demographic questionnaire (assessing age and the educational level) and General Health Questionnaire (GHQ) in 28 questions. Data were analyzed by SPSS 21 software using independent T test and Fisherchr('39')s exact test. Finding: The mean score of mental health was 30.17±12.85 in the veterans and 39.75±12.47 in the disables, which showed a significant difference and the mental health was better in the veterans (t=3.639; p<0.0001). In addition, the mean scores of mental health in the somatic symptoms, social dysfunction, symptoms of anxiety and sleep disorder and depression symptoms in the veterans were significantly higher than the disables (p<0.05). Conclusion: The mental health of the paraplegic veterans and disables is unfavorable. In addition, mental health of the non-veteran disabled persons is lower than the veterans.